Physicochemical and sensory properties of pempek made from narrow-barred spanish mackerel (Scomberomorus commerson) combined with barramundi (Lates calcarifer): Physicochemical and sensory properties of pempek made from narrow-barred spanish mackerel (Scomberomorus commerson) combined with barramundi (Lates calcarifer) - Nopianti, Rodiana; Widiastuti, Indah; Supriadi, Agus; Nugroho, Gama Dian; Lestari, Susi; Andini, Jesicha (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Pempek is a traditional food typical of the Palembang region in South Sumatra. Pempek is made from a mixture of ground fish and tapioca flour. This study aimed to determine the best formula for combining narrow-barred Spanish mackerel (Scomberomorus commerson) and barramundi (Lates calcarifer) based on the physical, chemical, and sensory characteristics of pempek. The experimental design was a randomized block design consisting of five treatment levels, each repeated three times: P1= 4:0, P2= 3:1, P3=2:2, P4= 1:3, and P5= 0:4. The research parameters used were proximate, physical, and sensory analyses. Proximate test results showed that the water content of pempek ranges from 53.65-56.27%, ash content 1.10-1.43%, fat content 0.35%-0.8%, protein content 7.05-8.42%, and carbohydrate levels 34.52-35.7%. The color test results for whiteness ranged from 54.90-59.32, lightness value 56.54-60.30, hue value 107.75-113.39°, and chroma value 8.89-13.17. The results of the pempek hardness test ranged from 22.7–24.87 N. The sensory test results for aroma were 5.08-5.36, and taste were 4.68-6.36. Based on all research parameters, the best combination of pempek was in treatment P4 (1:3).